2006
DOI: 10.1589/jpts.18.73
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lower-extremity Muscle Force, Muscle Mass and Asymmetry in Knee Extension Force on Gait Ability in Community-dwelling Elderly Women

Abstract: The purpose of this study was to examine the influence of muscle mass/power of the lowerextremities, including asymmetry in knee extension force, on gait ability of Japanese community-dwelling elderly women. The study population comprised 30 women aged 65-89 years. The parameters examined were activities of daily living, physical performance, functional capacity, isometric muscle forces of knee extension and flexion measured by a dynamometer, and muscle mass measured by bioelectrical impedance analysis. Asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…17,18,40 Muscle spindles are important proprioceptive structures that provide the nervous system with information about the muscle's length and velocity of contraction, which contributes to an individual's awareness of joint movement (kinesthesia) and joint position sense. 25,24 In this study, we found that fallers had significantly weaker ankle dorsifl exors on the left side than the nonfallers. Cutaneous mechanoreceptors, such as pacinian corpuscle and meisners corpuscle, are structures embedded in the superfi cial layers of the skin and provide the sense of light touch.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…17,18,40 Muscle spindles are important proprioceptive structures that provide the nervous system with information about the muscle's length and velocity of contraction, which contributes to an individual's awareness of joint movement (kinesthesia) and joint position sense. 25,24 In this study, we found that fallers had significantly weaker ankle dorsifl exors on the left side than the nonfallers. Cutaneous mechanoreceptors, such as pacinian corpuscle and meisners corpuscle, are structures embedded in the superfi cial layers of the skin and provide the sense of light touch.…”
Section: Discussionmentioning
confidence: 49%
“…24 We found that fallers presented with muscle force asymmetry in multiple muscle groups. Muscle force asymmetry can cause gait disorders, decreased balance, and an increased rate of falls.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Programs of assistance and prevention of d i s a b i l i t i e s h a v e b e e n p r o v i d e d b y l o c a l governments, and the achievements of those programs have been reported [9][10][11][12][13][14] . However, previous have studies often focused on ability to move as an indicator of decline in physical function, and rarely attended to other physical functions [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with sequelae of illness, it is essential to take c o m p e n s a t o r y m e a s u r e s a n d a r r a n g e a n environment with avoids decline of the level of independence in activities of daily living [30][31][32] . In addition to these measures, it is necessary to provide a program for sustainable functional improvement so that individuals can preserve function.…”
Section: Discussionmentioning
confidence: 99%